KEMAMPUAN MENENTUKAN KOMPOSISI SURAT PRIBADI DAN SURAT RESMI SISWA KELAS VII SMP NEGERI 10 TAPUNG KECAMATAN TAPUNG KABUPATEN KAMPAR - Harahap, Rina Tilawati; Hakim, Nursal; ', Auzar (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study investigated the ability to determine the composition of personal letters and official letters seventh grade students of SMPN 10 Tapung Tapung District of Kampar regency. This study aimed to obtain information that will be described regarding the ability to determine the composition of personal letters and official letters, and is there a significant difference between the ability to determine the composition of a personal letter and a composition of a formal letter. This study is a quantitative-descriptive. This research data is test data to determine the composition of personal letters and official letters seventh grade students of SMPN 10 Tapung Tapung District of Kampar regency. Instruments in this study is a chart of personal letters and official letters chart. The data collection was done by using the test. The population in this study were 147 students with the determination of a sample of 105 students. Data were analyzed with descriptive methods. In the form of exposure data and then normality test later if both data obtained by normal then paired sample t test. The validity of the data obtained through the method of data validation. Results of this study of the test results to determine the composition of personal letters and official letters seventh grade students of SMPN 10 Tapung Tapung District of Kampar regency. Judging from the two data obtained normality test is normal data. Then, out of paired samples t test was obtained 0.141 <1.660 t less than t table meaning there is no significant difference between the ability to determine the composition of personal letters and official letters because it is essentially the ability of determining the composition of the two letters the same, namely high category.Keyword: personal letters, official letters, normality test, paired sample t test.2